Melatonin Mediated Differential Regulation of Drought Tolerance in Sensitive and Tolerant Varieties of Upland Cotton (Gossypium hirsutum L.) - Supriya, Laha; Durgeshwar, Pullaiahgari; Muthamilarasan, Mehanathan; Padmaja, Gudipalli (Frontiers in Plant Science, 2022)
Melatonin (N-acetyl-5-methoxytryptamine), a biomolecule with multifunctional phyto-protectant activities, enhances the tolerance to broad-spectrum biotic and abiotic stresses in plants. However, little information is available on the effect of melatonin on different morpho-physiological, biochemical, and molecular parameters during drought stress incidence in varieties contrastingly differing in their tolerance levels. The present study is aimed at investigating the drought stress responses of drought sensitive (var. L-799) and drought tolerant (var. Suraj) varieties after exogenous melatonin priming and gaining mechanistic insights into drought tolerance in upland cotton (Gossypium hirsutum). Melatonin-priming enhanced the tolerance of L-799 to drought stress by modulating the antioxidant system, with increased photosynthetic activity, water-use efficiency, and nitrogen metabolism. Higher endogenous melatonin content and upregulated expression of candidate stress-responsive genes in primed L-799 suggested their involvement in drought tolerance. The higher expression of autophagosome marker [lipidated (ATG8-PE)] in melatonin-primed drought-stressed plants of L-799 also indicated the role of autophagy in alleviating drought stress. Interestingly, melatonin-priming did not show pronounced differences in the different parameters studied during the presence or absence of drought stress in Suraj. In conclusion, this study showed that melatonin plays an important role in mitigating drought stress effects by modulating several physiological, biochemical, and molecular processes, with the key regulatory factor being the plant tolerance level that serves as the switch that turns the priming effects on/off.